I am supposed to prove that $x\wedge x = x$ and $x\vee x = x$ follow from the other lattice axioms (associativity, commutativity and absorption).

So far I have $$x = x\vee(x\wedge x) = x\vee(x\wedge(x\wedge(x\vee x))) = x\vee ((x\wedge x)\wedge(x\vee x))$$

My argumentation then was that since $x=x\vee(x\wedge x)$ that either $x\vee x$ or $x\wedge x$ has to be equal to x, after which the other idempotent law would follow. The problem is, that can't be right - $x\vee(y\wedge z)= x$ can be true even though neither y nor z is equal to x (trivial example, $x\neq\emptyset,y=\emptyset,z=\emptyset, x\cup(y\cap z) = x$. I can't really think of anything else either though...


If $x$ can be written as $x=x\land y$ for any $y$, then we have $$x=x\lor (x\land y) =x\lor x.$$ Now choose $y:=(x\lor x)$.

  • $\begingroup$ You gotta love how these things always seem so stupidly obvious once someone tells you. $\endgroup$ – Cubic Nov 29 '12 at 0:06

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.